Natural Products in Medicinal Chemistry: Current Insights - Swain, Mahendra Pratap (AG Volumes, 2025)
Natural products have always been important to medicinal chemistry, and their importance hasn't waned. For thousands of years, plants have been used to make a variety of beneficial medications. This article reviews the various literature’s study on Natural Products and Medicinal Chemistry. It concluded that natural products remain a vital source for drug discovery, offering diverse scaffolds with unique bioactivities. Advances in chemical synthesis, biosynthetic engineering, and high-throughput screening have enhanced their optimization and accessibility. Despite challenges such as sustainability and bioavailability, innovative techniques in phytochemical analysis and medicinal chemistry are addressing these limitations. The integration of genomics and modern drug discovery approaches continues to expand therapeutic potential. As research progresses, plant-derived natural products will play a crucial role in developing novel, life-saving medications, reinforcing their significance in medicinal chemistry and future drug development.